"Fundamentals of ethnodesign" in the structure of training of students of specialty 6.020200. Design - Eyvas, L.F. (Pedagogy of Higher and Secondary Education, 2009)
In article the maintenance and the purposes of the program of a training course of "an ethnodesign Basis" for students of a speciality 6.020200 reveals. Design.